KOMPARASI METODE JARINGAN SYARAF TIRUAN SOM DAN LVQ UNTUK MENGIDENTIFIKASI DATA BUNGA IRIS - Meri Azm (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2014)
In this journal we tried to compare the performance between SOM & LVQ Methods of Neural Network. Iris data was used to perform the comparison. We found that SOM has better performance (89.33%) than LVQ (86.67%). But LVQ has faster time process(0.11 s) than SOM (0.20 s).